FRI0374 Outcomes in Systemic Lupus Erythematosus Patients with High Disease Activity Treated with Belimumab: 18 Month Results from the US Observe Study. (10th June 2014) - Collins, C.E.; Dall'Era, M.; Macahilig, C.; Pappu, R.; Molta, C.; Kan, H.; Koscielny, V.
Abstract : Background: Certain baseline factors in the BLISS trials were associated with high disease activity and identified as predictors of improved belimumab response. Objectives: We examined clinical effectiveness of belimumab 10 mg/kg plus standard therapy in systemic lupus erythematosus (SLE) patients with high disease activity in US clinical practice. Methods: OBSErve US (BLM117295) is a multicentre, retrospective, medical chart review study. Rheumatologists (n=92) randomly identified SLE patients who had received ≥8 belimumab infusions as part of usual care. Clinical measures were assessed 6 months (m) before belimumab initiation (index date), and every 6 m after, up to 2 years. Primary outcome was physician impression of overall change in SLE disease manifestations every 6 m, relative to the previous timepoint. Post hoc analyses examined three patient subgroups with high disease activity at index date: high anti-dsDNA and low complement (C3/C4); steroid dose ≥7.5 mg/day; SELENA-SLEDAI (SS) >10. Safety was not assessed. We present 18-m results. Results: Of the 501 patient charts examined at 0–6 m, 121 were lost to follow-up/had outstanding data and 46 discontinued by 12 m (multiple reasons permitted: 16 patient request, 12 medication not effective, 9 lack of patient compliance, 8 disease progression, 3 insurance/reimbursement loss, 2 sepsis, 2 depression). 334 patients remained at 12–18 m; at index date 70.7% received steroid doses ≥7.5 mg/day; 53.0% had high anti-dsDNA and low C3/C4; 74.5% of 102 patients with available SS data scored >10. Characteristics across groups at index date appear similar (Table). SLE disease manifestations improved from 12–18 m (Table 1 ); only changes in the high anti-dsDNA and low C3/C4 subgroup were significantly different vs the remaining sample. Since index date all groups had mean SS score reductions of ≥8.5 at 18 m (in patients with available data) and mean steroid dose reductions of ≥14.9 mg/day (Table 1 ). Conclusions: Based on physician impression, overall clinical response improved from 12–18 m with belimumab plus standard therapy; high anti-dsDNA and low C3/C4 patients had better responses vs the remaining sample. Disclosure of Interest: C. Collins Consultant for: GlaxoSmithKline, M. Dall'Era Consultant for: GlaxoSmithKline, C. Macahilig Grant/research support: GlaxoSmithKline, R. Pappu Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, C. Molta Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, H. Kan Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, V. Koscielny Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline DOI: 10.1136/annrheumdis-2014-eular.4968